Fundamental of Entrepreneurship ENT300 : Poppin's cupcake / Azilatul Fadzilah Abdull ... [et al.] - Abdull, Azilatul Fadzilah; Ismail, Nur Zurain; Kampon, Jacqueline Daisy; Manggi, Frescilla Natalia; Banai, Molly Lirek (2015)
Our company name is Poppin’s Cupcake. The business has been decided on the form of five partners. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to produce a healthy cupcake to the public. We will open our shop at The Summer Mall, Kota Samarahan and hopefully will be open to public on 1st January 2016.All partners are encourage and entitled to participate in all business management. We have agreed that Azilatul Fadzilah Abdullah is the General Manager , Nur Zurain Ismail as the Marketing Manager , Jacqueline Daisy as Administrative Manager , Frescilla Natalia as Operational Manager and Molly Lirek Banai as the Financial Manager .